Compensation-insurance has an effect on motivating employees - Misna Ariani; Dwinda Tamara (INOVASI, 2022)
Researchers want to know whether there is a relationship between non-physical work area environment, compensation guarantee, discipline, and work motivation. 80 employees who were sampled in the study on PT. Manissi Pratama Balikpapan. In carrying out their work, employees tend to use the Balikpapan Samarinda Toll Road (BalSam). Jobs that require high motivation and discipline because their work environment is a means of transportation for goods, where it takes a very short time to deliver or pick up goods or the mobility of people. The existence of the BalSam toll road can shorten the distance between Balikpapan-Samarinda by approximately 1 hour to 1 hour 30 minutes. Determination of the sample using the census method, so that all employees are sampled. Statement from employees used as data in this study. Partially work stimulus-motivation is influenced by work area-environment, reward-insurance, Discipline have a very meaningful effect.  Contribution of theory: the provision of compensation insurance motivates employees at work. The working environment of the BalSam toll road is full of high risk, insurance compensation is very appropriate to motivate employees. There is quite a strong attachment between insurance coverage and the work area-environment.